ТЕХНОЛОГИЯНЫҢ АДАМЗАТ ЖӘМИЙЕТИ МӘДЕНИЯТЫНЫҢ РАЎАЖЛАНЫЎЫНДАҒЫ ОРНЫ - Шамуратова, Т.; Авезов, Б.; Мадрахимова, Қ. (FAN va JAMIYAT, 2019)
The article is about developing technology culture, creativity and creative thinking in students through the study of technology in the teaching of the subject «Technology» in the teaching of technology classes.